Formulation Development of a Peel-Off Mask using Red Tilapia Fish (Oreochromis niloticus) Scale Gelatin as a Gelling Agent - Febianti Febianti; Fith Khaira Nursal; Hariyanti Hariyanti (Fakultas Farmasi Universitas Andalas, 2025)
Gelling agents are essential components in peel-off mask bases, with gelatin being a commonly used material. RedNile tilapia (Oreochromis niloticus) scales, a by-product of the fishery, have potential as a halal gelatin source. This study aimed to compare the characteristics of gelatin derived from red Nile tilapia scales (NTSG) with commercial gelatin (CG) as a gelling agent in peel off mask bases through their physical evaluation. Gelatin extraction and characterization were conducted, followed by the formulation of peel-off masks with gelatin concentrations of 6%, 8%, and 10%. NTSG characteristics met the Indonesian National Standard (ISN) and GMIA based on organoleptic properties, pH, ash content, moisture content, and gel strength. Gel physical characterisation revealed pH values of 5.7–5.9, a viscosity of 3500–6500 cP, a spreadability of 5–7 cm, an adhesion time of more than 4 seconds, and a drying time of 15–30 minutes. The results indicate that red Nile tilapia scales can produce gelatin suitable as a gelling agent on peel-off masks.